Frequency-Following Response with Speech Stimulus: Comparison between Two Methods of Stimulation - Sanguebuche, Taissane Rodrigues; Silva, Luize Caroline Lima da; Peixe, Bruna Pias; Silva, Débora Durigon da; Garcia, Michele Vargas (International Archives of Otorhinolaryngology, 2019)
Introduction Frequency-following response with speech stimulus (FFR-speech) is a subcortical potential that satisfactorily evaluates the processing of verbal information. However, there still are differences in the literature regarding its analysis and stimulation protocol.Objective To compare two stimulation protocols for the capture of FFR-speech, to identify the percentage of occurrence of the waves among them and to compare it with the specialized literature, as well as to describe the interpeaks of its waves.Method Considering the eligibility criteria, the sample consisted of 30 normal-hearing adults, with no complaints of speech comprehension. All of them were submitted to a basic audiological evaluation, to brainstem auditory evoked potential with click stimulus, and to FFR-speech. In the latter, 2 types of stimulation were performed, 3 series of 1,000 sweeps, and 2 series of 3,000 sweeps, for subsequent analysis of the resulting wave, in which we tried to mark the peak V followed by valleys A, C, D, E, F, and O.Results Differences in latency and interpeaks were not found between the protocols. In general, a higher occurrence of waves in the stimulation of 2 series of 3,000 sweeps was observed, but only the A valley presented a significant difference. When the values of the waves were compared with the literature, the V and A waves showed fewer occurrences in the present study.Conclusion The protocol of 2 series of 3,000 sweeps was better for FFR-speech in the studied equipment, considering the higher occurrence of waves, even though it is inferior to the specialized literature. Furthermore, it was possible to describe interpeak values and to observe no difference between the studied protocols
Keywords: hearing; electrophysiology; auditory evoked potentials; adult